Management of Colombian hotel companies' websites: an empirical approach - Eslava-Zapata, Rolando; Cárdenas, Diego; Chacón-Guerrero, Edixón (Universidad Pedagógica y Tecnológica de Colombia, 2023)
The article examines hotel companies' Website management in Cúcuta, Colombia. The methodology is quantitative with descriptive design. A survey of sixty-two items is applied to the managers of five hotels, to know their opinion on aspects such as: Website, Prices, Reservation, Products, Navigability, Customer Relationship Management Variables, Privacy and Security. The results indicate that hotels manage their websites well. However, weaknesses are evident in the visualization of room services, information on city attractions, interaction via chat and access for the visually impaired. We conclude with the need to constantly review the changing trends in web pages and clients' demands, in order to offer information that provides optimum visibility on the national and international market.